Histopathological description in Rattus norvegicus’s kindneys seropositives to Leptospira spp. - Jaramillo Delgado, Ingrid L. (2024)
The aim of this study was to describe the most common histopathological findings observed by Hematoxylin-Eosin staining in kidneys of Rattus norvegicus naturally infected and seropositive to Leptospira spp using the Microscopic Agglutination Test (MAT) technique. In total, 165 rodents were captured from three locations in Antioquia (Turbo and Medellín). Kidney samples were taken from the seropositive rodents by MAT and Hematoxylin-Eosin staining was used to evaluate the microscopic lesions and Warthin- Starry to visualize the bacteria. The most frequent morphological diagnoses were chronic interstitial nephritis (45.0%), followed by vascular congestion (20.1%) and chronic interstitial pyelonephritis (10.6%). The pathological processes were classified 73.1% as moderate and 26.9% as mild. The agent was not observed with the Warthin starry stain.